1966
DOI: 10.5006/0010-9312-22.5.143
|View full text |Cite
|
Sign up to set email alerts
|

Sulfurous Acid Corrosion of Low Carbon Steel at Ordinary Temperatures - I. Its Nature

Abstract: Corrosion rate data are presented for low carbon steel in (1) a combination of sulfur dioxide, water vapor and air, and (2) aqueous solutions of sulfurous acid in the absence of air, at ordinary temperature. Information as to the nature of the corrosion products is presented and it is shown that this depends on the place in which the corrosion takes place to an important extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1969
1969
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The exact mechanism of reduction of S02 is stil) unclear although possible reaction schemes have been proposed by Rozenfeld' and MeLeod and Rogers. 19 From the thermodynamic perspective, however, the detailed mechanism is inconsequential and the energetics of the overall reduction reaction are more important. The overall cathodic reduction process may be simply written as:…”
Section: Redox Potentials During the Tarnishing Reactionmentioning
confidence: 99%
“…The exact mechanism of reduction of S02 is stil) unclear although possible reaction schemes have been proposed by Rozenfeld' and MeLeod and Rogers. 19 From the thermodynamic perspective, however, the detailed mechanism is inconsequential and the energetics of the overall reduction reaction are more important. The overall cathodic reduction process may be simply written as:…”
Section: Redox Potentials During the Tarnishing Reactionmentioning
confidence: 99%
“…However, the formation of copper sulfide in an environment containing a moist oxidized sulfur species (SO2) requires explanation. Sulfur dioxide from the atmosphere dissolves readily in the water adlayer and the resulting sulfurous acid can act either as a reducing agent or an oxidizing agent (24). In fact, Rozenfeld (3) has shown that SO2 can act as a strong cathodic depolarizer by directly participating in the reduction reaction.…”
Section: ~Oo Z" _omentioning
confidence: 99%
“…22) McLeod and Rogers reported that SO 2 in the atmosphere easily dissolves into the surface electrolyte and that the resulting sulfurous acid (H 2 SO 3 ) can act either as a reducing agent or an oxidizing one. 27) We believe that there is a reduction route of bisulfite ions as follows. For copper, the bisulfite seen in the S 2p XPS spectra originated from SO 2 adsorption on the surface electrolyte, as shown in equation (1).…”
Section: )mentioning
confidence: 99%